Aktivitas dan Aktualisasi Diri Serta Pemenuhan Ke Informasi Mahasiswa Di Media Sosial - Robby Rachman Nurdiantara; Mira Renata; taufiq Furqon Nurhakim (KOMVERSAL, 2024)
This research was conducted to determine, describe and analyze the relationship between social media activity, self-actualization, and fulfilling the information needs of Halim Sanusi University Student of the 2023 class, using quantitative research methods with descriptive and simple linear regression analysis study designs. The research aims to understand the extent to which social media activities influence the level of self-actualization and fulfillment of students’ information needs. The sampling method applied was accidental sampling, where participants were selected randomly and without special consideration, but adjusted to the sample number obtained based on the Yamane sampling formula, from a total population of 327 people, was selected 180 samples of people. Data was collected through a questionnaire distributed online via Google Form to all students of the class of 2023 at Halim Sanusi University. Next, descriptive analysis was used to explore the profile social media activity of students, self actualization and information needs. Then a simple linear regression analysis was carried out to measure the effect of social media activities on the level of self actualization and the fulfillment information needs of students. The research results show various activities carried out by students, including searching for educational or knowledge content; entertainment; communicate, interact and socialize; looking for inspiration; seeking and sharing information, self actualization, and seeking various needs. Furthermore, the research results also show that social media activities have a significant effect on self actualization and fulfilling the information needs of student. It is hoped that the results of this research will provide a deeper understanding of the role of social media in the self-actualization process to form an identity and fulfilling the information needs of students. It is also hoped that the implications of these findings can contribute to the development of more effective support strategies in the context of higher education, especially at Halim Sanusi University and similar educational institutions.